A Study the Property of superparamagnetic property of nickel ferrite by Zinc doping as base to use in medical resonance imaging. - Fatani, Faiq (Journal of King Abdulaziz University: Science, 2024)
This paper add new step information study ability of work on dopant Zink by 0.01% to nano crystal of NiFe3O4 that has good VSM signal on 33% Ni and 67% Fe to check ability to use it as a base on MRI Contrast Agent. BY using Hydrothermal technique to prepare NiFexOy this type of preparation results in cubic ferrites structure depending on the purity and condition of preparation. This paper will show some results of this material structure with dopant of Zinck this utility used contrast agent base in a medical physics Magnetisation properties study for super spinel ferrites. Data analyzing by use tow examination X-Ray diffraction Analysis and vibrating Sample Magnetometer.